2010
DOI: 10.1098/rsbl.2010.0209
|View full text |Cite
|
Sign up to set email alerts
|

Cooperators benefit through reputation-based partner choice in economic games

Abstract: Explaining unconditional cooperation, such as donations to charities or contributions to public goods, continues to present a problem. One possibility is that cooperation can pay through developing a reputation that makes one more likely to be chosen for a profitable cooperative partnership, a process termed competitive altruism (CA) or reputation-based partner choice. Here, we show, to our knowledge, for the first time, that investing in a cooperative reputation can bring net benefits through access to more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
160
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(167 citation statements)
references
References 15 publications
4
160
2
1
Order By: Relevance
“…Hence assortment between cooperators could not arise. Reputation-based partner choice has been shown to promote cooperation in dyadic interactions (Fu et al, 2008;Sylwester & Roberts, 2010). An empirical study by Rockenbach & Milinski (2011) has looked at the effect of partner choice for future interactions in an n-person Prisoner's Dilemma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence assortment between cooperators could not arise. Reputation-based partner choice has been shown to promote cooperation in dyadic interactions (Fu et al, 2008;Sylwester & Roberts, 2010). An empirical study by Rockenbach & Milinski (2011) has looked at the effect of partner choice for future interactions in an n-person Prisoner's Dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…see Leimar & Hammerstein, 2001) if reputation is not only binary (either "good" or "bad") but comprises a third state "neutral" (Tanabe et al, 2013). Such a straightforward reputational mechanism enhances cooperation frequency and allows cooperative members of a group to recognise and trust each other (Nowak & Sigmund, 1998;Wedekind & Braithwaite, 2002;Wedekind & Milinski, 2000;Yoeli et al, 2013) and to benefit from choosing their partners (Fu et al, 2008;Sylwester & Roberts, 2010), creating a biological market based on cooperativeness, i.e. competition among potential partners to be chosen for social interactions (Barclay, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One 25 way this can be achieved is if helpful individuals are preferred as partners: giving players the option to either avoid bad partners or actively choose good ones increases cooperation, compared to interactions where individuals are forced to interact with one another [1][2][3][4][5]. Biological market theory [5][6][7] predicts that individuals prefer the 'best' possible partners for interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we often help individuals who helped us before (Trivers, 1971), but also choose to help individuals who act prosocially toward others (Alexander, 1987) and punish noncooperators (Fehr & Gächter, 2002). Experimental studies have confirmed that humans make their decisions about whom to cooperate with and help based on the other individual's reputation (Milinski et al, 2001(Milinski et al, , 2002Seinen & Schram, 2001;Wedekind & Milinski, 2000) and also invest in their own reputation to be preferably chosen as a cooperative partner (Sylwester & Roberts, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, as group size increases and direct encounters are less frequent or when direct assessment might be risky (e.g., when assessing the fighting abilities of others), it becomes more crucial to assess the reputation of others through indirect experiences like observing third-party interactions, and in the case of humans, by learning from gossip (Dunbar, 1986;Sommerfeld, Krambeck, Semmann, & Milinski, 2007). In human economic games, the reputation people form about others strongly influences their future cooperative behaviors toward those others (Hammerstein, 2003;Milinski, Semmann, & Krambeck, 2002;Nowak & Sigmund, 1998, 2005Panchanathan & Boyd, 2003;Tennie, Frith, & Frith, 2010;Wedekind & Milinski, 2000), and people even invest in their own reputation which allows them to be preferably chosen as cooperative partners (Roberts, 2008;Sylwester & Roberts, 2010).…”
mentioning
confidence: 99%